Age-changes in right ventricular function–pulmonary circulation coupling: from pediatric to adult stage in 1899 healthy subjects. The RIGHT Heart International NETwork (RIGHT-NET) - Vriz, Olga; Veldman, Gruschen; Gargani, Luna; Ferrara, Francesco; Frumento, Paolo; D’Alto, Michele; D’Andrea, Antonello; Radaan, Sarah Aldosari; Cocchia, Rosangela; Marra, Alberto Maria; Ranieri, Brigida; Salzano, Andrea; et al. (The International Journal of Cardiovascular Imaging, 2021)
The present study analyzes age-specific changes in RV function and RV–PA coupling in a large cohort of apparently healthy subjects with a wide age-range, to identify reference values and to study the influence of clinical and echocardiographic cofactors. 1899 Consecutive healthy subjects underwent a standardized transthoracic echocardiographic examination. Tricuspid annular plane systolic excursion (TAPSE) and systolic pulmonary artery pressure (SPAP) were measured. Ventriculo-arterial coupling was then inferred from the TAPSE/SPAP ratio. A quantile regression analysis was used to estimate quantiles 0.05, 0.10, 0.50 (median), 0.90, and 0.95 of TAPSE, SPAP and TAPSE/SPAP. The association between age and each of these values was determined. The mean age of the group was 45.2 ± 18.5 years (range 1 to 102 years), 971 were males. SPAP increased with age, whereas TAPSE and TAPSE/SPAP ratio decreased. Upon multivariate modeling, the most significant positive associations for TAPSE were body surface area (BSA) driven by the pediatric group, stroke volume (SV), E/A and negatively heart rate and E/e′ ratio. SPAP was positively associated with increasing age, SV, E/A, E/e′ and negatively with BSA. TAPSE/SPAP ratio was negatively associated with age, female sex, and E/e′ and positively with BSA. A preserved relationship between TAPSE and SPAP was found across the different age groups. TAPSE, SPAP and TAPSE/SPAP demonstrate important trends and associations with advancing age, impaired diastolic function, affected by female sex and BSA However the relationship between TAPSE and SPAP is relatively well preserved across the age spectrum.